2015
DOI: 10.1186/s12936-015-0631-5
|View full text |Cite
|
Sign up to set email alerts
|

Parasite accumulation in placenta of non-immune baboons during Plasmodium knowlesi infection

Abstract: BackgroundPlacental malaria (PM) causes adverse pregnancy outcomes in the mother and her foetus. It is difficult to study PM directly in humans due to ethical challenges. This study set out to bridge this gap by determining the outcome of PM in non-immune baboons in order to develop a non-human primate model for the disease.MethodsTen pregnant baboons were acquired late in their third trimester (day 150) and randomly grouped as seven infected and three non-infected. Another group of four nulligravidae (non-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Miller et al . described extensive P. knowlesi schizogony in several tissues in rhesus monkeys (Miller et al 1971 ), and more recent studies showed P. knowlesi iRBC distribution in baboon tissues (Ozwara et al 2003 ; Onditi et al 2015 ). Additionally, unlike P. falciparum and P. coatneyi , the P. knowlesi variant antigens are not concentrated at parasite-induced protrusions at the RBC surface (reviewed in Galinski and Corredor, 2004 ).…”
Section: The Host Matters: the In Vivo Environmentmentioning
confidence: 99%
“…Miller et al . described extensive P. knowlesi schizogony in several tissues in rhesus monkeys (Miller et al 1971 ), and more recent studies showed P. knowlesi iRBC distribution in baboon tissues (Ozwara et al 2003 ; Onditi et al 2015 ). Additionally, unlike P. falciparum and P. coatneyi , the P. knowlesi variant antigens are not concentrated at parasite-induced protrusions at the RBC surface (reviewed in Galinski and Corredor, 2004 ).…”
Section: The Host Matters: the In Vivo Environmentmentioning
confidence: 99%
“…However, the mTOR inhibitor failed to impede inflammation. Further research on the role of mTOR is necessary in placental malaria animal model, such as the baboon, where Plasmodium knowlesi have been shown to sequester to the placenta [ 83 ]. On the other hand, in vitro studies using the BeWo cell line exposed to malaria-associated cytokines plus chemokines (secreted by human monocytic cell line (THP1) cells that were incubated with P. falciparum infected red blood cells) induced dysregulation of mTOR pathway [ 61 ], suggesting that mTOR pathway in ST might be interfered by placental malaria-inflammatory-cytokines.…”
Section: Placental Malaria and Syncytiotrophoblast Functionsmentioning
confidence: 99%
“…Because Papio sp. are widely used as an animal model to study human reproduction (including placental infection-related pathologies;Onditi et al, 2015) because of their high similarities in placental structure and fetal development(Bauer, 2015), infection with B. papionis in these primatesmight constitute a relevant in vivo model to study Brucella-induced placental disorders. Interestingly, B. papionis replicates actively within human CTB or SYN but only survives in EVT.…”
mentioning
confidence: 99%